Hubungan Dampak Media Sosial terhadap Kejadian Menarche Dini pada Remaja Putri di SMP Negeri 1 Yogyakarta - Pingky Citra Mahardika Ali; Yekti Satriyandari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Early menarche is defined as the onset of first menstruation before the age of 12 years and is increasingly observed among adolescent girls. Early menarche may lead to various adverse physical and psychological health outcomes later in life. One factor suspected to contribute to the occurrence of early menarche is exposure to social media. This study aimed to determine the relationship between social media exposure and the occurrence of early menarche among adolescent girls. This study employed an observational analytic method with a cross-sectional approach. The population consisted of all eighth-grade female students at SMP Negeri (State Junior High School) 1 Yogyakarta, totaling 132 students, with a sample of 57 students selected using purposive sampling. Data were analyzed using the Chi-square test (Fisher’s Exact Test). The results of the Chi-square analysis yielded a p-value of 0.001 (p < 0.05) and a Phi (φ) coefficient of 0.456, indicating a statistically significant relationship with a moderate level of association between the impact of social media and the occurrence of early menarche. In conclusion, there is a significant relationship between the impact of social media exposure and the incidence of early menarche among female adolescents at SMP Negeri 1 Yogyakarta.